2018
DOI: 10.1561/101.00000101
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Electricity on Economic Development: A Macroeconomic Perspective

Abstract: We find that electricity use and access are strongly correlated with economic development, as theory would suggest. Despite large empirical literatures and suggestive case evidence, there are, however, few methodologically strong studies that establish causal effects on an economy-wide basis. There is some evidence that reliability of electricity supply is important for economic growth. We propose that future research focuses on identifying the causal effects of electricity reliability, infrastructure, and acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(27 citation statements)
references
References 71 publications
(105 reference statements)
0
27
0
Order By: Relevance
“…As the development of the electricity sector and economic growth as strongly correlated, it is very important to increase the ability to achieve economic independence based on domestic resources. Burke et al (2018) discovered some evidence that electricity supply reliability is essential for economic growth and recommended that the causal effects of electricity reliability, infrastructure, and access on economic growth be identified (Burke et al, 2018;Yoo and Kim, 2006). Hansen et al (2020) suggested that LCR should be used as part of renewable energy auction schemes in order to promote local industrial development, while Allan et al (2020) investigated LCR policy scenarios that would not only stimulate economic activity but also contribute significantly to the government's net zero emission goal, especially in the future development of offshore wind (Negara, 2016).…”
Section: Local Content Requirement (Lcr)mentioning
confidence: 99%
“…As the development of the electricity sector and economic growth as strongly correlated, it is very important to increase the ability to achieve economic independence based on domestic resources. Burke et al (2018) discovered some evidence that electricity supply reliability is essential for economic growth and recommended that the causal effects of electricity reliability, infrastructure, and access on economic growth be identified (Burke et al, 2018;Yoo and Kim, 2006). Hansen et al (2020) suggested that LCR should be used as part of renewable energy auction schemes in order to promote local industrial development, while Allan et al (2020) investigated LCR policy scenarios that would not only stimulate economic activity but also contribute significantly to the government's net zero emission goal, especially in the future development of offshore wind (Negara, 2016).…”
Section: Local Content Requirement (Lcr)mentioning
confidence: 99%
“…As Burke et al (2018) argue, electricity has offered advantages over other energy sources, enabling far more efficient technologies (like the information and communications technologies), a more productive organization of manufacturing and a more efficient lighting and providing productivity gains. To make the best of these advantages, a reliable supply of electricity and an adequate electricity network that answers to the volatile demand of electricity will be necessary.…”
Section: Economic Growth and Electricitymentioning
confidence: 99%
“…For all these reasons, the relationship between electricity and economic growth is an important issue to research, and the empirical evidence is inconclusive. Camarero et al (2015) classify the research approaches into groups based on different estimations.…”
Section: Economic Growth and Electricitymentioning
confidence: 99%
“…Labor productivity is a key element for assessing the standard of living of those engaged in production processes in which labor remains the single most important input (OECD, 2001). While larger firms might be able to substitute other electricity resources (Foster & Steinbuks, 2009), this choice would be limited for smaller firms since providing small-scale electricity is generally costly (Burke, Stern & Bruns, 2018). Further, MSEs are more financially constrained compared with larger firms, thus it is less likely that MSEs have their own captive generators.…”
Section: The Impact Of Blackouts On the Performance Of Micro And Smalmentioning
confidence: 99%